Are bulimia nervosa and binge eating disorder increasing? Results of a population‐based study of lifetime prevalence and lifetime prevalence by age in South Australia. (15th February 2020) - Bagaric, Marija; Touyz, Stephen; Heriseanu, Andreea; Conti, Janet; Hay, Phillipa
Abstract: Objective: This study aimed to provide updated lifetime prevalence estimates of eating disorders, specifically bulimia nervosa (BN) and binge eating disorder (BED) and investigate changes over time in lifetime prevalence by age. Method: Two thousand nine hundred seventy‐seven participants from South Australia were interviewed in the Health Omnibus Survey. DSM‐5 criteria were used for current and broad (in accord with the International Statistical Classification of Diseases and Related Health Problems‐11 [ICD‐11]) criteria for lifetime prevalence of BED. Results: This study found that the lifetime prevalence of BN was 1.21% (95% CI [0.87, 1.67]) and 2.59% (95% CI [2.07, 3.22]) for males and females, respectively, and that lifetime prevalence for BED‐broad was 0.74% (95% CI [0.49, 1.11]) and 1.85% (95% CI [1.42, 2.40]) for males and females, respectively, which is higher than reported in previous research. Current prevalence (past 3 months) of BN was 0.40% (95% CI [0.23, 0.70]) and 0.81% (95% CI [0.54, 1.20]) for males and females, respectively, and current prevalence for BED was found to be 0.03 (95% CI [0.01, 0.04]) and 0.20% (95% CI [0.09, 0.44]) for males and females, respectively. Conclusions: The current study confirmed the moderate community prevalence of BN and BED. BED was found to be less prevalent than BN in the present study, and a significant lifetime prevalence by age effect was found for both. Lifetime prevalence by age indicated that past increases in prevalence may be waning in this century and that overall BN and BED are not increasing in Australia.